2021
DOI: 10.3389/fbioe.2021.662979
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Fatty Acid Profile, Morphology, and Tetraacetylphytosphingosine-Forming Capability Between Wild-Type and Mutant Wickerhamomyces ciferrii

Abstract: One tetraacetylphytosphingosine (TAPS)-producing Wickerhamomyces ciferrii mutant was obtained by exposing wild-type W. ciferrii to γ-ray irradiation. The mutant named 736 produced up to 9.1 g/L of TAPS (218.7 mg-TAPS/g-DCW) during batch fermentation in comparison with 1.7 g/L of TAPS (52.2 mg-TAPS/g-DCW) for the wild type. The highest production, 17.7 g/L of TAPS (259.6 mg-TAPS/g-DCW), was obtained during fed-batch fermentation by mutant 736. Fatty acid (FA) analysis revealed an altered cellular FA profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…TesA overexpression significantly promoted the synthesis of LCFA in C. glutamicum but adversely affected LCFA production in E. coli . Some studies have reported the production of FFA with different carbon lengths by the TE AcTesA in E. coli and Synechocystis [ 29 ]. The differences in FA content and composition might be related to their heterologous expression.…”
Section: Resultsmentioning
confidence: 99%
“…TesA overexpression significantly promoted the synthesis of LCFA in C. glutamicum but adversely affected LCFA production in E. coli . Some studies have reported the production of FFA with different carbon lengths by the TE AcTesA in E. coli and Synechocystis [ 29 ]. The differences in FA content and composition might be related to their heterologous expression.…”
Section: Resultsmentioning
confidence: 99%
“…6 D). Therefore, the observed diauxic growth pattern, which led to a reduced conversion yield and titer of melanin, might be avoided by optimizing feeding strategies in fed-batch fermentation of an F. kingsejongi strain constitutively expressing HPPD [ 37 , 38 ]. Furthermore, genetic inactivation of the hmg gene encoding homogentisate 1,2-dioxygenase, which further oxidizes homogentisate to fumarate and acetoacetate, might enhance the titer of melanin produced by F. kingsejongi .…”
Section: Resultsmentioning
confidence: 99%